P431 Effect of targeted intervention on condom use and among men who have sex with men (MSM) taking PrEP in nairobi kenya. (14th July 2019) - Akolo, Maureen
Abstract : Background: In 2017 Kenya became the second country in Africa to roll out PrEP. It prioritized Key population to access free PrEP services. Sex Workers Outreach Program (SWOP) - a HIV/STI research center offers preventive, care and treatment services to female sex workers and MSM within Nairobi. In 2018 SWOP realized high STI cases among MSM on PrEP and introduced an intervention seeking to improve their STI prevention knowledge. Methods: An experimental study was carried out among HIV negative MSM enrolling into PrEP within SWOP clinics. Participants were randomized to control and intervention. Control group received PrEP services as prescribed by the government; the intervention group received targeted health education in addition to government prescribed services. Both arms were followed up for six months and screened for STIs at every visit. Data were collected at baseline and endline using structured questionnaire. Results: 168 MSM enrolled into study with 84(50%) on each arm. At baseline condom use and STI Knowledge was low across both arms. At endline knowledge level had improved significantly in intervention arm compared to control arm with significance association to the targeted health education: Used K.Y Jelly to lubricate condom χ2=4.983, df=1, P=0.026. Knew how to use male condoms Fisher's<0.001. Used condom consistently χ2=0.92, df=1, P=0.337. Negotiate for condom use χ2=28.886, df=1 P<0.001. Negotiated condom use with regular clients χ2=8.839, df=1, P=0.003. Refused sex when client refused condom use χ2=11.483, df=1, P=0.001. Syndromically STI cases at month one were 28/84 (33.3%) in control, while 26/84 (30.9%) in intervention arm. At month six cases were 16/38(42%) control and 7/59(12%) in intervention arm. Conclusion: Targeted health education on condom use among MSM on PrEP is vital in averting STI cases. Disclosure: No significant relationships.